Integration of Remote Sensing and GIS for Archaeological Investigations - Maktav, D.; Crow, J.; Kolay, C.; Yegen, B.; Onoz, B.; Sunar, F.; Coskun, G.; Karadogan, H.; Cakan, M.; Akar, I; Uysal, C.; Gucluer, D.; et al. (IOS PRESS, 2010)
The western hinterland of the modern city of Istanbul contains some of the most remarkable monuments of ancient and medieval hydraulic engineering dating from the fourth to the twelfth centuries AD, including lines of aqueduct channels and bridges extending up to 336 km to the west of the modern city. Until recently fieldwork has been limited and only within the last two decades have there been serious attempts to map the complexity of the monuments and water lines. The dense forest which covers much of the northern hills of Thrace is a major factor restricting fieldwork and survey, yet at the same time the woodland ensures the preservation of much of the system. Two previous studies of the water supply system have been able to identify the major spring sources, to map the line of the water supply channels and to record and locate over sixty bridges which are a key component of the system. However these studies have been constrained as they are not able to integrate adequately this survey data. The new research programme between Istanbul Technical University (ITU) and Edinburgh University commenced in 2007 and includes all existing GPS data and archaeological observations to be incorporated as part of a modern GIS combining the topographical and hydraulic information available from 1:25 000 digital maps with a wide range of high and medium resolution remotely sensed data. Further surface GPS based archaeological survey has been undertaken over the past two years and has been able document a significant number of the extant channels and bridges. Using high resolution IKONOS images and orthophotos it has been possible to create a textured land surface of forests and fields for the Thracian digital surface model (DSM) in which to situate the various monuments and channels of the water supply system. This digital resource is now capable of providing the basis for future archaeological documentation and analysis and two case studies are given. Integrated with multi-spectral data this gives the opportunity to view the system in its wider setting and also to identify major urban and landscape changes impacting on the long-term conservation and management of the ancient remains.
Keywords: Remote Sensing